Parental Involvement and Pupils’ Academic Performance in the Cape Coast Metropolis, Ghana - Darko-Asumadu Daniel Ampem; Sika-Bright Solomon (Open Education Studies, 2021)
Studies have shown that pupils’ academic performance is not only determined by their parents’ socio-economic status but also parental involvement in the education processes. The study, therefore, examined the socio-economic status of parents and its influence on pupils’ academic performance looking at the role of parental involvement in that relationship. With Walberg’s theory of educational productivity as a lens, the findings were based on surveys with 120 pupils selected randomly from Kwaprow Basic School and 10 and 5 interviews with parents and teachers respectively. The study found that parents’ education did not significantly affect students’ academic performance. Parents were not assisting their children in their academic activities including failure to attend Parent-Teacher Association meetings and not assisting them with homework. This was largely attributed to parental low educational level. However, with a 0.045, 0.028, 0.041 and 0.036, as p-values, the study showed that there was a statistically significant relationship between parental involvement, occupation and family size and academic performance of pupils. In order to improve students’ academic performance, the study recommended that the Parent-Teacher Associations (PTA) should intensively sensitise parents on the need to involve themselves in their wards’ education so as to aid them to perform better academically.